Board attributes, risk management, and firm performance : an analysis of listed financial service firms in Nigeria - Kakanda, Mahmud Mohammed (2017)
The purpose of this study is to examine the relationship between board attributes and risk management (committee structure, practice, and disclosure) and firm performance (return on asset [ROA], return on equity [ROE], and market-to-book ratio [MTB]) of listed financial service firms in Nigeria from the year 2012 to 2016. Data were collected from the annual accounts and reports of 45 sampled firms (225 firm-year observations). To test the hypotheses developed in this study, the Panel Corrected Standard Errors (PCSEs) regression was used. The result from the multivariate analysis shows that board size and risk management committee meeting have a significant positive effect on firm performance (ROA, ROE, and MTB), while chief executive officer’s tenure has a significant positive effect on ROA and ROE. However, board composition, board expertise, risk management committee size, and risk management practice and disclosure have a significant negative impact on all the three performance variables in this study. While board meeting has an insignificant positive effect on ROA and MTB and has an insignificant negative influence on ROE. Risk management committee composition shows an insignificant positive association with firm performance. Consequently, the result of this study portrays the influence of Corporate Governance (CG) mechanisms (board attributes and risk management) in the Nigerian financial institutions. In addition, the findings of this study offer an immense insight to the regulators of CG reforms in Nigeria to review and strengthen the existing CG code where necessary. Besides, this study has also provided an important intuition to the shareholders, corporate managers, financial analysts, and the academic communities to further understand the impact of CG mechanisms on firm performance.